2021
DOI: 10.1007/s11357-021-00358-6
|View full text |Cite
|
Sign up to set email alerts
|

A ride through the epigenetic landscape: aging reversal by reprogramming

Abstract: Aging has become one of the fastest-growing research topics in biology. However, exactly how the aging process occurs remains unknown. Epigenetics plays a significant role, and several epigenetic interventions can modulate lifespan. This review will explore the interplay between epigenetics and aging, and how epigenetic reprogramming can be harnessed for age reversal. In vivo partial reprogramming holds great promise as a possible therapy, but several limitations remain. Rejuvenation by reprogramming is a youn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 220 publications
(228 reference statements)
1
15
0
Order By: Relevance
“…Expressing so called Yamanaka factors, OCT4, SOX2, KLF4 and c-MYC (OSKM) converts somatic cells into induced pluripotent stem cells (iPSCs). Ocampo et al have shown the potential of partial reprogramming in tackling aging [97][98][99]. Unlike previous studies that used Yamanaka factors in vivo which could initiate cancer development or teratoma formation, Ocampo and his co-workers have successfully demonstrated that tumor formation can be avoided by shortterm induction of OSKM.…”
Section: Cellular Reprogrammingmentioning
confidence: 99%
“…Expressing so called Yamanaka factors, OCT4, SOX2, KLF4 and c-MYC (OSKM) converts somatic cells into induced pluripotent stem cells (iPSCs). Ocampo et al have shown the potential of partial reprogramming in tackling aging [97][98][99]. Unlike previous studies that used Yamanaka factors in vivo which could initiate cancer development or teratoma formation, Ocampo and his co-workers have successfully demonstrated that tumor formation can be avoided by shortterm induction of OSKM.…”
Section: Cellular Reprogrammingmentioning
confidence: 99%
“…Furthermore, Ocampo et al demonstrated that partial reprogramming, achieved by transient, periodic induction of OSKM (2 days on, then 5 days off, repeated several times), ameliorates signs of ageing without loss of cellular identity [ 74 ]. They conducted partial reprogramming first on progeroid (model for HGPS) mouse fibroblasts and alleviated age-associated hallmarks, such as DNA damage, nuclear envelope damage, dysregulation of histone modifications, stress and senescence associated factors, and mitochondrial-associated reactive oxygen species (ROS) production (cellular and epigenetic differences between aged and young cells and tissues are reviewed in detail in [ 121 , 122 ]). Similar rejuvenation of dysregulated histone modifications was also observed when transient reprogramming was conducted on high-passage human fibroblasts (derived from iPSCs).…”
Section: Reprogramming-induced Epigenetic Rejuvenationmentioning
confidence: 99%
“…Important CpG sites are overwhelmingly closer to CTCF binding sites (Supplementary Figure S4). This suggests that epigenetic alterations proximal to such loci may alter chromatin packing by affecting CTCF binding, as chromatin structure modifications have been associated with aging [26].…”
Section: Resultsmentioning
confidence: 99%
“…This observation suggests that epigenetic alterations proximal to such loci that are involved in chromatin packing by affecting CTCF binding may be captured by AltumAge. This result is relevant because chromatin structure modifications have been associated with aging (see review [31]).…”
Section: Altumage Captures Relevant Age-related Cpg-cpg Interactionsmentioning
confidence: 99%